The degree of teachers/specialists’ knowledge and application of evidence-based practices for autism spectrum disorder in autism centers in the city center of Erbil - Ali, Sirwan Wali (Edelweiss Applied Science and Technology, 2025)
The current study aimed to describe the degree of teachers' and specialists' knowledge and application of practices based on scientific research for autism spectrum disorder in autism centers in the city center of Erbil. The number of participants in the study reached 99. To achieve the aim of the study, the researcher built two scales: a scale of evidence-based practices and the other a scale of procedures for selection strategy. Their validity and reliability were verified. The descriptive survey method was used to answer the study questions. The results indicated that the degree of knowledge and application of evidence-based practices was moderate and that the relationship between knowledge and application of practices was high. While the relationship between knowledge and how to choose the therapeutic strategy was moderate. The study recommended the need to train teachers and specialists on evidence-based practices and how to choose them, as well as to use other variables such as teachers' experiences and the degree of disorder.